Boundary-layer instability and transition on a flared cone in a Mach 6 quiet wind tunnel. (1st January 2013) - Hofferth, Jerrod; Saric, William; Kuehl, Joseph; Perez, Eduardo; Kocian, Travis; Reed, Helen
Measurements of boundary-layer transition location and boundary layer profiles on a sharp-tipped 5º-half-angle flared cone were made in a low-disturbance Mach 6 wind tunnel. Uncalibrated boundary-layer profiles of mean and fluctuating voltage representative of mass flux are obtained using constant temperature hot-wire anemometry at several axial locations, and are notionally compared with preliminary simulations. Spectral energy content is observed between 250 and 310 kHz – the first measurements of frequencies typical of the second mode instability at Texas A&M. Growth of this high-frequency content is compared with N-factor results from linear parabolised stability equation (LPSE) computations. Possible sources of disagreement between the experimental and computed frequencies for second-mode growth are discussed, as are future improvements to the hotwire anemometry technique. Nevertheless, the successful measurement of high-frequency content highlighted here constitutes an important step toward acquisition of calibrated measurements of hypersonic boundary-layer instabilities to be used as code validation.